Ecoregion as an object of cross-border and regional planning of biodiversity protection systems - Білоус, Людмила Федорівна (Київський національний університет імені Тараса Шевченка, 2017)
Розглянуто оселищну концепцію охорони біорізноманіття, історію становлення та зміст систем класифікації оселищ суші, прісноводних та морських. Інформацію про оселищне різноманіття визначено ключовою при виділенні екорегіонів. Екорегіон запропоновано визначати в якості об’єкту конструктивно-географічного планування систем охорони біорізноманіття. Екорегіон є базовою територіальною одиницею планування екомереж NATURA 2000, EMERALD. Запропоновано огляд екорегіонів України. Їх визначено об’єктами транскордонного співробітництва в галузі охорони довкілля й біорізноманіття та планування національних, регіональних й локальних систем природоохорони. Визначено пріоритетні задачі України з впровадження оселищної концепції охорони біорізноманіття в розрізі екорегіонів.

The habitat concept of nature conservation was considered. The history of formation and content of classification systems of the terrestrial habitats, the freshwater habitats and the marine habitats were outlined. Information on the habitat diversity was identified as a key in the selection of ecoregions. The ecoregion was considered as an object of the constructive-geographical planning of the nature protection systems. It was noted that the World Wildlife Fund (WWF) had been studied types of habitats in Europe and had allocated 867 terrestrial ecoregions, 830 freshwater ecoregions and 232 marine ecoregions. The ecoregion was determined by a key area of ecological network planning NATURA 2000, EMERALD. The review of ecoregions of Ukraine was proposed. 12 ecoregions were defined as existing on the territory of Ukraine. The terrestrial ecoregions are represented by European mixed forests, the Eastern European forest steppe, Pontic steppe, Crimean Submediterranean forest complex, Carpathian montane forests, Pannonian mixed forests. The freshwater ecoregions are represented by Central & Western Europe, Dniester – Lower Danube, Dnieper – South Bug, Crimea Peninsula, Don. The marine ecoregion plays an important role in the nature protection system of Ukraine. This ecoregion is the Mediterranean Sea Ecoregion. The Black and Azov seas belong to its composition. WWF has identified a list of Global 200 that contains 238 ecoregions (142 terrestrial, 53 freshwaters, 43 marines) priority for the protection of their habitat diversity and biodiversity. More than half of these ecoregions are marked as endangered. The habitats of two ecoregions from the Global 200 list are in Ukraine. These are the habitats of the terrestrial ecoregion European-Mediterranean Montane Forests (the mountainous territories of the Crimean and Carpathian regions) and the freshwater ecoregion Danube River Delta. The ecoregions of Ukraine are defined by the objects of cross-border cooperation in the field of environmental protection and planning of regional and local environmental protection systems. It was noted that any environmental protection planning decisions in the ecoregion were carried out in connection with its information portfolio. Information about: protected areas; habitat, biodiversity; terrestrial, freshwater, marine priorities for ecoregions are obligatory components of the portfolio. It was noted that the informational portfolio of the ecoregion was created for establishing an effective interstate environmental partnership. The priority tasks of Ukraine for implementing the habitat concept of nature conservation were determined.
Екорегіон як об’єкт транскордонного й регіонального планування систем охорони біорізноманіття
Інформаційна система природи Європейського Союзу [Електронний ресурс]. – Режим доступу : http://eunis.eea.europa.eu/ Типи оселищ Інформаційної система природи Європейського Союзу [Електронний ресурс]. – Режим доступу : http://eunis.eea.europa.eu/habitats-code-browser.jsp?expand= – level_G Карта екорегіонів суші [Електронний ресурс]. – Режим доступу : http://wwf.panda.org/about_our_earth/ecoregions/maps/ Прісноводні екорегіони [Електронний ресурс]. – Режим доступу : http://wwf.panda.org/about_our_earth/about_freshwater/freshwater_ecoregions/ Морські екорегіони [Електронний ресурс]. – Режим доступу : http://wwf.panda.org/about_our_earth/ecoregions/about/habitat_types/selecting_marine_ecoregions/ Спісок екорегіонів пріоритетної охорони оселіщного різноманіття [Електронний ресурс]. – Режим доступу : http://www.worldwildlife.org/publications/global-200
Keywords: оселище; класифікація оселищ; оселищне різноманіття; біорізноманіття; екорегіон; екомережа; екомережа NATURA 2000; екомережа EMERALD; список Global 200; система охорони біорізноманіття; habitat; habitat classification; habitat diversity; biodiversity; ecoregion; ecological network; NATURA 2000; EMERALD; Global 200; biodiversity protection system